Strategi Pembelajaran Berbasis Proyek dalam Menguatkan Hasil Belajar Afektif Pada Mata Pelajaran Pendidikan Agama Islam (PAI) di SMP Negeri 3 Kutowinangun - Rochmah, Lailatur; Subarkah, Imam (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
The objectives of this study are: (1) to analyze and describe the project-based learning strategy applied in Islamic Religious Education (PAI) subjects at SMP Negeri 3 Kutowinangun, especially in strengthening students' affective learning outcomes. (2) to analyze the obstacles of project- based learning strategies in strengthening affective learning outcomes in PAI subjects at SMP Negeri 3 Kutowinangun. (3) to analyze solutions to the obstacles of project-based learning strategies in strengthening affective learning outcomes in PAI subjects at SMP Negeri 3 Kutowinangun. This research uses a descriptive qualitative approach with a case study. The subjects in this study were Islamic Religious Education teachers and eighth-grade students of SMP Negeri 3 Kutowinangun in the 2024/2025 academic year. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that: (1) A project-based learning strategy has been implemented by emphasizing active student involvement in contextual and collaborative learning activities, such as buying and selling simulations, creating Islamic value posters, and group presentations; (2) Obstacles encountered include time constraints, lack of facilities, and teacher readiness in designing projects integrated with affective objectives; (3) The solutions implemented include strengthening learning planning, collaboration between teachers, and developing simple projects relevant to students' life contexts